The Prevalence of Rome IV Nonerosive Esophageal Phenotypes in Children - Mahoney, Lisa B. (J Pediatr, 2017)
OBJECTIVES: To assess the prevalence of Rome IV nonerosive esophageal phenotypes in children using multichannel intraluminal impedance testing and to describe the rates of proton pump inhibitor (PPI) responsiveness and the frequency of microscopic esophagitis in these patients. STUDY DESIGN: We conducted a retrospective review of all children ≥5 years of age who underwent esophagogastroduodenoscopy and multichannel intraluminal impedance testing off PPI therapy for evaluation of typical gastroesophageal reflux symptoms. Only children with symptoms during the multichannel intraluminal impedance testing were included. Children were categorized into the following nonerosive esophageal phenotypes using Rome IV criteria: nonerosive reflux disease, reflux hypersensitivity, and functional heartburn. Rates of esophagitis and responsiveness to acid suppression therapy were assessed. RESULTS: Forty-five children were included: 27% were categorized as having nonerosive reflux disease, 29% with reflux hypersensitivity (27% acid and 2% nonacid), and 44% with functional heartburn. Older children reported significantly more heartburn (P < .001) than younger children, whereas younger children were more likely to report nonspecific pain (P = .047). There were no differences between groups in other reflux symptoms, rates of responsiveness to PPIs, or the presence of microscopic esophagitis on biopsy. CONCLUSIONS: Functional heartburn is the most common Rome IV nonerosive esophageal phenotype in children. Neither microscopic esophagitis nor PPI responsiveness can predict phenotype in pediatric patients.